La inimputabilidad de los adolescentes infractores, y su incidencia socio-jurídica, en la ciudad de Piñas, en los años 2010-2011. - Astudillo Blacio, Mariana de Jesús (2013)
Finally reference to the development of the legal framework, where we will present a proposal with a desire to provide legal support for the issue in question, and mainly incorporated into the Penal Code the issue makes older adolescents aged 16 years and under 18 you are fully charged in crimes against life.